1984
DOI: 10.1161/01.atv.4.4.303
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, biochemical, and genetic features in familial disorders of high density lipoprotein deficiency.

Abstract: P lasma high density lipoproteins (HDL, density = 1.063 -1.21 g/ml) mostly have alpha mobility on lipoprotein electrophoresis, and are composed (weight %) of approximately 50% protein, 25% phospholipid, 20% cholesterol (mainly esterified), and triglyceride. 1 " 1 Fluctuations in HDL levels have been associated largely with alterations in HDL (d = 1.063-1.125 g/ml). 5 Cholesterol is the HDL constituent commonly measured (following precipitation of other lipoproteins), and decreased plasma HDL cholesterol conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(50 citation statements)
references
References 131 publications
1
48
0
1
Order By: Relevance
“…A number of previous observations suggest metabolic processes that might contribute to the correlations involving HDL 2 subspecies reported here. It has been reported that the fractional catabollc rate of HDL 2 (especially HDI-a) is Inversely related to levels of triglyceride or VLDL 17 possibly accounting for the reciprocal relations of HDLj and VLDL changes. Furthermore, levels of HDLj, 16 and more recently larger LDL, 19 have been positively correlated with levels of adipose tissue lipoprotein lipase.…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous observations suggest metabolic processes that might contribute to the correlations involving HDL 2 subspecies reported here. It has been reported that the fractional catabollc rate of HDL 2 (especially HDI-a) is Inversely related to levels of triglyceride or VLDL 17 possibly accounting for the reciprocal relations of HDLj and VLDL changes. Furthermore, levels of HDLj, 16 and more recently larger LDL, 19 have been positively correlated with levels of adipose tissue lipoprotein lipase.…”
Section: Discussionmentioning
confidence: 99%
“…The biochemical mechanism(s) behind this observed relationship is still unknown but is believed to be related to the role of HDL in promoting the transport of cholesterol from peripheral tissues to the liver for catabolism (reverse cholesterol transport) (3), thus preventing the accumulation of excess cellular cholesterol and the development of foam cells. Although this putative role of HDL in reverse cholesterol transport has not been proven conclusively, this concept is supported by many of the clinical features found in patients with HDL deficiency (4). Furthermore, in vitro studies have shown that HDL can promote cellular cholesterol efflux (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Marked HDL deficiency states (HDL cholesterol , 5 mg/dl) and undetectable plasma apolipoprotein A-I (apoA-I) levels have been reported in humans as a result of mutations at the APOA1/C3/A4 gene locus (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Such patients lack apoA-I-containing HDL in plasma, with normal or decreased triglyceride levels, normal LDL cholesterol levels, and often strikingly premature CHD (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Other patients with marked HDL deficiency have mutations affecting the apoA-I sequence that can affect the activity of lecithin:cholesterol acyl transferase activity (19)(20)(21)(22)(23)(24)(25)(26).…”
mentioning
confidence: 99%